2006
DOI: 10.1016/j.tsf.2005.07.137
|View full text |Cite
|
Sign up to set email alerts
|

Sub-bandgap optical absorption spectroscopy of hydrogenated microcrystalline silicon thin films prepared using hot-wire CVD (Cat-CVD) process

Abstract: Hydrogenated microcrystalline silicon (Ac-Si:H) thin films with different silane concentration (SC) have been prepared using the HW-CVD technique. Dual beam photoconductivity (DBP), photothermal deflection spectroscopy (PDS), and transmission measurements have been used to investigate the optical properties of the Ac-Si:H films. Two different sub-bandgap absorption, a(hm), methods have been applied and analyzed to obtain a better insight into the electronic states involved. A good agreement has been obtained i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…On the other hand, the SiO x films are highly transparent in the optical wavelength range of interest so they have negligible effect on the data in our experimental methods, in particular steady-state photonconductivity and defect spectroscopy with the DBP method. Sub-bandgap absorption coefficient spectra obtained using DBP are a powerful tool to investigate the changes in the occupation of defect states in the light-soaked and annealed states of a-Si:H films [11] and are also very sensitive to study bulk defects in c-Si:H films [12]. Preliminary results obtained with the DBP method indicated that reversible and irreversible changes created by water and (or) oxygen exposure can be detected by the changes in the sub-bandgap absorption coefficient spectrum [13].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the SiO x films are highly transparent in the optical wavelength range of interest so they have negligible effect on the data in our experimental methods, in particular steady-state photonconductivity and defect spectroscopy with the DBP method. Sub-bandgap absorption coefficient spectra obtained using DBP are a powerful tool to investigate the changes in the occupation of defect states in the light-soaked and annealed states of a-Si:H films [11] and are also very sensitive to study bulk defects in c-Si:H films [12]. Preliminary results obtained with the DBP method indicated that reversible and irreversible changes created by water and (or) oxygen exposure can be detected by the changes in the sub-bandgap absorption coefficient spectrum [13].…”
Section: Introductionmentioning
confidence: 99%
“…Among these deposition methods, CBD technique is one of the least expensive and simplest methods, which makes it very attractive to obtain reproducible and uniform CdS films . On the other hand, the presence of moisture is an important parameter for degradation on the conversion efficiency and lifetime of CdS solar cells . Therefore, the effect of the humidity level should be considered during the lamination process …”
Section: Introductionmentioning
confidence: 99%
“…The absorption coefficient at low energy of 0.8 eV (α(0.8 eV)) is sensitive to the defect density of states in the gap of a-Si thin films, the lower the α(0.8 eV), the lower the defect density of states [12,13,18]. Figure 5 shows the α(0.8 eV) evolution of the a-Si:H thin films deposited with different assisted-ion beam gases.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 6 shows the Eg of the a-Si thin films deposited with different assisted-ion beam gases [18,19]. It was observed that the Eg of a-Si:H thin films deposited without assisted-ion-beam and with…”
Section: Resultsmentioning
confidence: 99%